Description of the nymph of Thraulodes sternimaculatus Lima, Mariano & Pinheiro, 2013 (Leptophlebiidae: Ephemeroptera) from Northeastern Region of Brazil - Nascimento, Stênio R. S.; Lima, Lucas R. C.; Azevêdo, Carlos A. S. (Zootaxa, 2019)
Thraulodes Ulmer, 1920 is one of the most abundant and widespread genera of Leptophlebiidae represented by 66 species (Barber-James et al. 2013; Gonçalves et al. 2013; Lima et al. 2013; Souto et al. 2014; Zúñiga et al. 2015; Boldrini et al. 2018; Campos & Mariano 2019). Its distribution extends from Central Argentina in the Neotropics to the Neartic Region. For Brazil, 23 species are known (Salles & Boldrini 2019), but only seven species are known from both adult and nymphal stages: T. bonito Gonçalves, Da-Silva & Nessimian; T. cochunaensis Domínguez; T. daidaleus Traver & Edmunds; T. jones Gonçalves, Da-Silva & Nessimian; T. itatiajanus Traver & Edmunds; T. schlingeri Traver & Edmunds and T. traverae Thew (Thew 1960; Traver & Edmunds 1967; Domínguez 1987; Lopes et al. 2003; Gonçalves et al. 2010; Gonçalves et al. 2013).